The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2169/internalmedicine.4755-20
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly Cases Exhibiting Increased Growth Hormone Levels during Oral Glucose Loading with Preadministration of Dipeptidyl Peptidase-4 Inhibitor

Abstract: Objective Glucose-dependent insulinotropic polypeptide (GIP) is speculated to worsen growth hormone (GH) hypersecretion in acromegaly and to be a cause of paradoxical increases in GH (PI-GH) during 75-g oral glucose tolerance testing (75-g OGTT). Dipeptidyl peptidase-4 inhibitors (DPP4is), which increase the circulating concentration of active GIP, are frequently administered to diabetic patients, including those with acromegaly. We aimed to determine whether or not the administration of a DPP4i i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…A recent multicentric study compared the efficacy of the combination of DPP4-i (sitagliptin) and GLP1-RA (liraglutide) vs. insulin treatment, as second-line therapy after metformin, showing the superiority of the first arm of treatment ( 122 ). However, another study showed that use of DPP4-i was associated with an increase in GH secretion, and therefore these drugs need to be used with caution ( 166 ).…”
Section: Acromegalymentioning
confidence: 99%
“…A recent multicentric study compared the efficacy of the combination of DPP4-i (sitagliptin) and GLP1-RA (liraglutide) vs. insulin treatment, as second-line therapy after metformin, showing the superiority of the first arm of treatment ( 122 ). However, another study showed that use of DPP4-i was associated with an increase in GH secretion, and therefore these drugs need to be used with caution ( 166 ).…”
Section: Acromegalymentioning
confidence: 99%